2020
DOI: 10.3389/fendo.2020.00504
|View full text |Cite
|
Sign up to set email alerts
|

Hypertriglyceridemia and Atherosclerosis: Using Human Research to Guide Mechanistic Studies in Animal Models

Abstract: Human studies support a strong association between hypertriglyceridemia and atherosclerotic cardiovascular disease (CVD). However, whether a causal relationship exists between hypertriglyceridemia and increased CVD risk is still unclear. One plausible explanation for the difficulty establishing a clear causal role for hypertriglyceridemia in CVD risk is that lipolysis products of triglyceride-rich lipoproteins (TRLs), rather than the TRLs themselves, are the likely mediators of increased CVD risk. This hypothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 193 publications
2
31
0
Order By: Relevance
“…23 However, the expression data of these pathway proteins in the liver, such as GPAT1 (lipogenesis), MTTP (lipoprotein secretion) and PT1 (fatty acid β-oxidation), and the plasma β-hydroxy butyrate levels suggest the role of lipoprotein lipase (LPL)-mediated extrahepatic tissue clearance of plasma triglyceride in regulating hypertriglyceridemia, as the lipoprotein lipase (LPL) present in the vascular bed of adipose tissue and muscle involves in the uptake of triglyceride from the triglyceride-rich lipoproteins by lipolytic action and thus regulates triglyceride levels in the circulation. 24 Interestingly, the rats that received carrot juice exhibited a reduction of adiposity and leptin content, which corroborated with elevated retinol concentration of the adipose tissue. In line with adiposity reduction, the ingestion of carrot juice or withdrawal of high fructose in the diet normalized hyperinsulinemia and C-peptide levels without impacting the plasma glucose levels, thus reflected in improved insulin sensitivity as indicated by the HOMA-IR index and plasma RBP4 levels; one of the markers of insulin sensitivity.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…23 However, the expression data of these pathway proteins in the liver, such as GPAT1 (lipogenesis), MTTP (lipoprotein secretion) and PT1 (fatty acid β-oxidation), and the plasma β-hydroxy butyrate levels suggest the role of lipoprotein lipase (LPL)-mediated extrahepatic tissue clearance of plasma triglyceride in regulating hypertriglyceridemia, as the lipoprotein lipase (LPL) present in the vascular bed of adipose tissue and muscle involves in the uptake of triglyceride from the triglyceride-rich lipoproteins by lipolytic action and thus regulates triglyceride levels in the circulation. 24 Interestingly, the rats that received carrot juice exhibited a reduction of adiposity and leptin content, which corroborated with elevated retinol concentration of the adipose tissue. In line with adiposity reduction, the ingestion of carrot juice or withdrawal of high fructose in the diet normalized hyperinsulinemia and C-peptide levels without impacting the plasma glucose levels, thus reflected in improved insulin sensitivity as indicated by the HOMA-IR index and plasma RBP4 levels; one of the markers of insulin sensitivity.…”
Section: Discussionmentioning
confidence: 76%
“…23 However, the expression data of these pathway proteins in the liver, such as GPAT1 (lipogenesis), MTTP (lipoprotein secretion) and PT1 (fatty acid β-oxidation), and the plasma β-hydroxy butyrate levels suggest the role of lipoprotein lipase (LPL)-mediated extra-hepatic tissue clearance of plasma triglyceride in regulating hypertriglyceridemia, as the lipoprotein lipase (LPL) present in the vascular bed of adipose tissue and muscle involves in the uptake of triglyceride from the triglyceride-rich lipoproteins by lipolytic action and thus regulates triglyceride levels in the circulation. 24 …”
Section: Discussionmentioning
confidence: 99%
“…However, the location of atherosclerotic lesions in mice is different from that in humans. In the mouse model, plaques locate in the aortic sinus and innominate arteries, while the coronary arteries and carotid arteries are the primary lesions in human ( Zhao et al, 2020b ; Basu and Bornfeldt, 2020 ). The experimental models involved in this review can indeed explain the potential mechanisms of TCM in treating atherosclerosis via antioxidants.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, basic studies suggested that small RLP particles, which contain 5–20 times more cholesterol than LDL, had a greater affinity for subendothelial components. The TRL remnants could be taken up by macrophages directly without modification, thus promoting rapid cholesterol accumulation in lesional macrophages ( 22 , 112 ). TRL remnants are also proposed to exacerbate the atherosclerotic process by inducing the secretion of TNF-α and IL-1β ( 113 ), activating the coagulation cascade ( 114 ), impairing endothelium-dependent vasodilation ( 115 ), and increasing oxidative stress ( 116 ).…”
Section: Biomarkers For Atherosclerotic Diseases Using Qnmr Metabolomicsmentioning
confidence: 99%
“…Many large epidemiological studies have supported that triglycerides (TGs) correlate with CVD risk ( 15 17 ), although the association is sometimes attenuated with adjustment for other traditional risk factors ( 18 ). However, increasing evidence now has highlighted the importance of triglyceride-rich lipoproteins (TRLs) and their remnants, both in fasting and nonfasting periods ( 19 22 ). Populations with mild-to-moderately elevated nonfasting TG levels have increased risks for ischemic stroke, myocardial infarction, ischemic heart disease, and all-cause mortality ( 23 25 ).…”
Section: Introductionmentioning
confidence: 99%